Komunitas Algae Epilitik Sebagai Indikator Biologis Di Sungai Batang Ombilin, Sumatera Barat - Indah Yusliga Sari Purba; Izmiarti Izmiarti; Solfiyeni Solfiyeni (Universitas Andalas, 2015)
A study about community of epilithic algae was conducted on April until August 2014. The objective of this study was to clarify composition and structure of epilithic algae in Ombilin River and water quality of Ombilin River based on community of epilithic algae. Samples were collected by survey and brushing method and the research station was choosed 6 stations purposively. The results showed that totally 72 genera had been found with total density of epilithic algae was 388.92ind/cm2to 2139.04 ind/cm2. The highest density of epilithic algae was found in station III (Talawi) and the lowest in station II (Lubuk Pinang). The dominant epilithic algae were Cocconeis, Synedra, Navicula, Denticula and Gomphonema (Baccilariophyta), Stigeoclonium (Chlorophyta), Phormidium and Calothrix (Cyanophyta), Ceratium (Dinophyta) and Audouinella (Rhodophyta). Diversity index was 1.50 to 2.48, where the highest was observed at station II (Lubuk Pinang) and the lowest one at station III (Talawi). Equitability index was 0.42 to 0.68. Similarity index was 50 to 74.70%. Saphrobic coefficient was 0.61–1. The result also showed that Ombilin Riverwere polluted slightly byorganic and inorganic materials in β-mesosaprobic phase.